From Night to Light: A Bibliometric Analysis of the Global Research Trajectory of Sleep Disorders in Parkinson’s Disease - Shi L; Zhao X; Wu J; He C (Journal of Multidisciplinary Healthcare)
Luya Shi,1,2 Xinxin Zhao,3 Jing Wu,3 Caidi He1 1Department of Nursing, Municipal Hospital Affiliated to Taizhou University, Taizhou, Zhejiang, 318000, People’s Republic of China; 2Department of Post Graduate School of Nursing, Sehan University, Yeonggam, 58447, South Korea; 3Department of Nursing, The Second Affiliated Hospital of Shandong University of Traditional Chinese Medicine, Jinan, 250001, People’s Republic of ChinaCorrespondence: Caidi He, Municipal Hospital Affiliated to Taizhou University, Taizhou, Zhejiang, 318000, People’s Republic of China, Email hcdeye@gmail.comPurpose: Sleep disorders are prevalent non-motor symptoms in patients with Parkinson’s disease (PD), significantly diminishing the overall quality of life for patients and potentially accelerating the deterioration of motor and cognitive functions, accelerating disease progression. Despite increasing research on sleep disorders in PD, a comprehensive analysis of the knowledge structure and key issues in this field are still lacking. This study aims to identify research hotspots and emerging trends related to sleep disorders in PD through a detailed bibliometric analysis.Patients and Methods: On October 1, 2024, an extensive search was conducted in the Web of Science Core Collection (WOSCC) database to gather relevant literature on sleep disorders in PD. Bibliometric and knowledge mapping analyses were performed using CiteSpace, VOSviewer, and bibliometrix.Results: Between January 1, 2004, and October 1, 2024, a total of 3,655 publications on sleep disorders in PD were published by 3,387 institutions across 87 countries. The volume of publications has shown a steady increase, a trend projected to continue. Current research is primarily centered on Neurosciences, Pharmacology, and Clinical Neurology. Emerging trends involve comprehensive evaluations of sleep, early diagnosis and prevention of various sleep disorder subtypes in PD, and advancing research through animal models to develop effective therapies. Emerging keywords include machine learning, sleep quality, biomarkers, covid-19, and mouse model.Conclusion: This bibliometric analysis sheds light on the global landscape of PD-related sleep disorder research over the past two decades, highlighting key countries, institutions, authors, and journals driving advancements in the field. Moreover, it uncovers pivotal research hotspots and emerging trends, offering valuable insights and guidance for scholars engaged in this area.Keywords: bibliometric analysis, CiteSpace, Parkinson’s disease, REM sleep behavior disorder, restless leg syndrome, sleep disorder